2015
DOI: 10.5455/2349-3933.ijam20150515
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome in pregnancy induced hypertension cases at GMERS Medical College, Dharpur-Patan, North Gujarat region, India: a prospective study

Abstract: Pregnancy is a physiological phenomenon for most women. However, some develop problems during its evolution, putting both the mother's and the conceptus' health at sake. Pregnancy-induced hypertension is one of the maternal diseases that cause the most detrimental effects to the maternal, fetal, and neonatal organisms. Pregnancy-induced hypertension is the general classification for hypertension diseases during pregnancy, which include pregnancy-induced hypertension (without proteinuria), preeclampsia (with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Almost similar finding was reported in study conducted by Gandhi et al at Dharpur-Patan showed that 48.4% had labour pain, 11.6% had convulsion, 10.5% had no any complain, 9.5% had oedema feet and 6.3% headache and bleeding per vagina (6.3%). 10 In present study among PIH patients 85.93% and 98.43% of had mild PIH with systolic B.P. 140-160 mmHg and diastolic B.P.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…Almost similar finding was reported in study conducted by Gandhi et al at Dharpur-Patan showed that 48.4% had labour pain, 11.6% had convulsion, 10.5% had no any complain, 9.5% had oedema feet and 6.3% headache and bleeding per vagina (6.3%). 10 In present study among PIH patients 85.93% and 98.43% of had mild PIH with systolic B.P. 140-160 mmHg and diastolic B.P.…”
Section: Resultsmentioning
confidence: 46%
“…9 In contrast to this different study conducted by Gandhi et al and Khosravi et al 43.15% among primiparous 56.85% multiparous and 32.8% PIH mother are nullipara while 67.2% were multipara respectively. 10,12 In our study among PIH mother we found that 48.44% had lower abdominal pain, 18.75% had vomiting/epigastric discomfort followed by headache (12.50%), convulsion (10.94%), no any complain (10.94%), oedema feet (9.37%), dizziness (7.81%). Almost similar finding was reported in study conducted by Gandhi et al at Dharpur-Patan showed that 48.4% had labour pain, 11.6% had convulsion, 10.5% had no any complain, 9.5% had oedema feet and 6.3% headache and bleeding per vagina (6.3%).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Eclampsia was responsible for maximum number of preterm deliveries 58.3% followed by severe preeclampsia 50%, which is comparable with the studies by Gandhi M et al, Bangal V et al and by George JN et al where in, the incidence was 29%, 37%, and 31% respectively (Table 9). 5,9,10 This indicates that severity of the disease is directly related to the prematurity of the baby. 32 out of 182 cases in this study had Apgar <6 (17.5%) at 1 min and 22 out 182 cases in this study had Apgar <8 (11.9%) at 5 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Tufnell et al reported 65.3% incidence of prematurity. 11 The high incidence of preterm delivery could be attributed to the early intervention and induction of labour or LSCS done to avert further maternal and perinatal complications.…”
mentioning
confidence: 99%